Symbiotic bacteria associated with entomopathogenic nematodes showed molluscicidal activity against Biomphalaria glabrata, an intermediate host of Schistosoma mansoni - Jiranun Ardpairin; Chanakan Subkrasae; Abdulhakam Dumidae; Supawan Pansri; Chanatinat Homkaew; Wipanee Meesil; Tewarat Kumchantuek; Ittipon Phoungpetchara; Adler R. Dillman; Coralie Pavesi; Helge B. Bode; Sarunporn Tandhavanant; et al. (Parasites & Vectors)
Abstract Background Biomphalaria glabrata acts as the intermediate host of schistosomes that causes human schistosomiasis. Symbiotic bacteria, Xenorhabdus and Photorhabdus associated with Steinernema and Heterorhabditis, produce secondary metabolites with several biological activities. Controlling B. glabrata is a potential strategy to limit the transmission of schistosomiasis. The aims of this study were to identify Xenorhabdus and Photorhabdus bacteria based on recA sequencing and evaluate their molluscicidal activity against B. glabrata snail. Results A total of 31 bacterial isolates belonging to Xenorhabdus (n = 19) and Photorhabdus (n = 12) (X. ehlersii, X. stockiae, X. indica, X. griffinae, P. luminescens, P. akhurstii, and P. laumondii subsp. laumondii were molecularly identified based on recA sequencing. Five isolates of bacterial extracts showed potential molluscicide, with 100% snail mortality. P. laumondii subsp. laumondii (bALN19.5_TH) showed the highest effectiveness with lethal concentration (LC) values of 54.52 µg/mL and 89.58 µg/mL for LC50 and LC90, respectively. Histopathological changes of the snail were observed in the head–foot region, which showed ruptures of the epithelium covering the foot and deformation of the muscle fiber. A hemocyte of the treated snails was observed in the digestive tubules of the digestive glands. The hermaphrodite glands of treated snails showed a reduction in the number of spermatozoa, degeneration of oocytes, and deformation and destruction in the hermaphrodite gland. In addition, liquid chromatography–tandem mass spectrometry (LC–MS/MS) of three symbiotic bacteria contained compounds such as GameXPeptide, Xenofuranone, and Rhabdopeptide. Conclusions Five bacterial extracts showed good activity against B. glabrata, especially P. laumondii subsp. laumondii and X. stockiae, which produced virulent secondary metabolites resulting in the death of the snails. They also caused histopathological alterations in the foot, digestive glands, and hermaphrodite glands of the snails. This study suggests that extracts from these bacteria show promise as molluscicides for the control of B. glabrata. Graphical abstract